Polotsk cadet corps during the World War I (1914–1918) - Lukashevich, Andrei M. (Journal of the Belarusian State University. History, 2024)
The article examines the fate of the Polotsk Cadet Corps during the World War I. It is shown that in September 1914, in connection with the use of the buildings of the educational institution for the treatment of the wounded, the cadet corps was evacuated by company to Sumy (3rd company), Moscow and then Odessa (2nd company) and Vladikavkaz (1st company). There, the Polotsk residents were assigned to local secondary military educational institutions. General M. G. Chigir, along with the office and archives of the corps, remained in Polotsk for another year, and only in September 1915, due to the worsening situation at the front, was evacuated to Simbirsk. The fate of each company is traced, the degree of their adaptation to new living conditions and the formation of relationships with students of local corps are described. It is noted that in Sumy and Vladikavkaz, strained relations arose between the Polotsk residents and students of host educational institutions, due to different traditions, mentality and upbringing. The reforming of the Polotsk Cadet Corps in 1917 into a military department gymnasium and the admission of students under new democratic conditions is shown. It is concluded that until October 1917, the Polotsk gymnasium of the military department functioned as a single military educational institution. And only after the Bolsheviks came to power, who abandoned the reform of the Provisional Government, it was officially abolished.